2017
DOI: 10.1093/beheco/arx127
|View full text |Cite
|
Sign up to set email alerts
|

Indirect genetic effects in behavioral ecology: does behavior play a special role in evolution?

Abstract: Behavior is rapidly flexible and highly context-dependent, which poses obvious challenges to researchers attempting to dissect its causes. However, over a century of unresolved debate has also focused on whether the very flexibility and context-dependence of behavior lends it a unique role in the evolutionary origins and patterns of diversity in the Animal Kingdom. Here, we propose that both challenges can benefit from studying how indirect genetic effects (IGEs: the effects of genes expressed in one individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
127
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(135 citation statements)
references
References 118 publications
(168 reference statements)
7
127
1
Order By: Relevance
“…These findings support the notion that behavior, and the evolutionary rates thereof, might be particularly prone to variation in the social environment (Bailey et al. ), compared to other aspects of the environment such as predation threats. We employed a pedigreed full‐sib/half‐sib breeding design over two generations to assess the heritability and evolvability of different behaviors across two environments, one in which crickets were exposed to silence and one in which they were exposed to male acoustic sexual signals.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…These findings support the notion that behavior, and the evolutionary rates thereof, might be particularly prone to variation in the social environment (Bailey et al. ), compared to other aspects of the environment such as predation threats. We employed a pedigreed full‐sib/half‐sib breeding design over two generations to assess the heritability and evolvability of different behaviors across two environments, one in which crickets were exposed to silence and one in which they were exposed to male acoustic sexual signals.…”
supporting
confidence: 87%
“…; Bailey et al. ). Here, we found that variation in the social environment (the presence or absence of male acoustic sexual signals) had substantial effects on estimates of behavioral heritability and evolvability in the Australian field cricket ( Teleogryllus oceanicus ).…”
Section: Discussionmentioning
confidence: 98%
“…More generally, accumulating evidence for IGE and GxG epistasis in many systems (Bijma ; Bailey et al. ) suggests that social genetic effects and interactions are pervasive. These effects are generally overlooked in theory exploring the maintenance of genetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…Our illustration for simplicity assumes that ψ represents a unidimensional form of plasticity although we appreciate that it is typically multidimensional in nature (Bailey et al. ).…”
mentioning
confidence: 99%